MERAYAKAN NASIONALISASI HOSPITALITAS MELALUI PENGHIDUPAN CROSS-SIPLISITAS UMAT PENTAKOSTAL MASA KINI - Reynhard Malau (Bethel Press, 2023)
This research examines the stigma and marginalization of certain groups regarding the presence and contribution of Pentecostalism in Indonesia as an Indonesian citizen who is part of a global Christian denomination. This research aims to show the argumentative basis of Amos Yong's thinking about hospitality as an inter-subjective and communal experience for global and national communities. This research method is qualitative research. The data was obtained through Amos Yong's thoughts. The research findings show that although hospitality is confined within localities in each region, at the same time, it is a global context itself by removing one by one the segregative barriers within the global space. Through its hospitality actions, Pentecostalism was able to answer the differences in non-productive stigma on a national scale when it clashed with the nationalization of Pentecostalism in Indonesia with all its suspicions about its contribution and axiology.